Electron spin ensemble strongly coupled to a three-dimensional microwave cavity - Abe, E; Wu, H; Ardavan, A; Morton, J (2011)
We demonstrate the strong coupling between an electron spin ensemble and a three-dimensional cavity in a reflection geometry. We also find that an anticrossing in the cavity/spin spectrum can be observed under conditions that the collective coupling strength gc is smaller than the spin linewidth γs or the cavity linewidth. We identify a ratio of gc to γs (gc / γs 0.64) as a condition to observe a splitting in the cavity frequency. Finally, we confirm that gc scales with N, where N is the number of polarized spins. © 2011 American Institute of Physics.